When ethnolinguistics breaks out of academia. A report from Africa and international cooperation - Micheli, Ilaria (Antropologia Pubblica, 2018)
After having been relegated to the austere halls of academia for centuries, in the last decades human sciences have more and more frequently been called to get mixed up with the outside world. With its focus on people and on their relations, anthropology (Appadurai 1996; 2014; Latour 2006; 2012) has represented one of the most brilliant examples of the fruitfulness of this evasion, specifically in the field of international cooperation (Olivier de Sardan 2005; Fassin 2012). In this report I will try to argue that, in a multi-disciplinary perspective, a joint anthropological and ethnolinguistic approach to the field can be very productive. An attentive and well focused lexical mapping of specific domains, can in fact help to significantly reduce the time anthropologists usually spend in data gathering through participant observation and face to face interviews. This approach seems particularly useful when funds are object-driven and the time scheduled for the analysis of the context quite insufficient. I will try to demonstrate this thesis through the discussion of two case studies: 1. a preservation project among the Ogiek communities of the Mau Forest in Kenya, and 2. a medical project designed for the Hamar and Dhaassanach peoples of Ethiopia.